Public intimacy - Mateus, Samuel (2010)
Modernity has established a strong focus on individual making intimacy a central dimension of privacy. Intimacy was the place where an inner-self was formed and where singularity was obtained apart from the public and from society. Interior meant an inward and isolated space of self-definition and personality development. In contemporary societies intimacy is being public. As public and private domains merge, interior and exterior become mixed. We call this extimacy as intimate and exterior become simultaneous. Unlike modern thesis, intimacy seems only to be complete when it is exhibited in public domain. We examine contemporary public intimacy by distinguishing two types of extimacy while highlighting the subjectiveness and mediatisation processes.